The Integration of Technology on Family Dynamics and Communication Pattern - Abdullahi, Shehu Abdulkadir; Judith, Okara Chibugo; Okon, Onukak Wisdom (Lembaga Yasin AlSys, 2025)
This research paper explores the multifaceted impact of technology on family dynamic patterns, focusing on how digital advancements have reshaped communication, relationships, and interactions within families. The study identifies both positive and negative influences of technology. Technology facilitates and enhances communication through social media and instant messaging, offering families the ability to connect across distances. It can reduce face-to-face interactions; lead to an increase dependence on technology usage. This research will examine the impact of technology on family communication. The study will employ a method of quantitative survey method to assess the integration of technology among different families alongside its variance across different family structures and socioeconomic statuses. The findings suggest that while technology presents challenges to traditional family dynamics, it also offers opportunities for growth and adaptation. The paper concludes with recommendations for families and policymakers to navigate the evolving digital landscape, emphasizing the need for balance and mindful usage of technology to support healthy family relationships.